Penjajahan Negara-Negara Barat Atas Negara-Negara Islam - Muhammad Fajar Rasyiid S; Siti Nurzana; Zaini Dahlan (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
Islamic culture has been on a steady decline from the time of the prophet, who ushered in its golden age. A factor contributing to Islamic stagnation was the emergence of Western nations that colonized Islamic nations. In their imperialistic pursuit of power, wealth, culture, and politics, Western nations prey on Islamic nations. Consequently, it is intriguing to examine their colonization of Islamic nations. My goal in writing this paper is to gain a better understanding of the reasons behind western colonization of Islamic countries. I hope that all students in Indonesia, and particularly those at UINSU, will read it and be inspired to work towards a world where Islamic countries no longer face colonization from the West.. Library research is the methodology employed in this article. There was a lengthy period of Islamic stagnation due to the colonization of the archipelago by western powers. This was accompanied by devastating conflicts, economic and social inequalities, the loss of native culture and civilization, and the introduction of Christianity. Due in part to the fact that Islamic countries are unable to stand up to Western colonization on their own, Islam has been unable to advance in recent centuries. Economic, social, political, and legal decisions may all stem from the need for prior permission from the federal government in order to pass legislation pertaining to a state. A number of indigenous peoples' desires to secede from their colonial masters emerged in response to Western colonialism. Some of the colonized states that rose up in opposition to the occupying power were successful in becoming independent nations, while others were unable to do so due to the superior military might of the colonial power.